3‐Nitro‐2‐pyridinesulfenates as Efficient Solution‐ and Solid‐Phase Disulfide Bond Forming Agents. Issue 34 (29th May 2017) - Taguchi, Akihiro; Kobayashi, Kiyotaka; Kotani, Akira; Muguruma, Kyohei; Kobayashi, Misaki; Fukumoto, Kentarou; Takayama, Kentaro; Hakamata, Hideki; Hayashi, Yoshio
Abstract: In this paper, a new disulfide‐forming agent based on the finding that alkoxy 3‐nitro‐2‐pyridinesulfenates (Npys‐OR) can oxidize thiol groups is reported. Methyl 3‐nitro‐2‐pyridinesulfenate (Npys‐OMe), which is easily prepared from 3‐nitro‐2‐pyridinesulfenyl chloride in a one‐step reaction and has a reduction peak potential ( E pc ) of −0.541 V versus Ag/AgCl, produces the cyclic nonapeptide oxytocin from its linear form in good yield (92 %) with minimal oligomer formation. Npys‐OMe in the solid phase also demonstrated excellent results in oxytocin synthesis. Other disulfide‐containing peptides, such as α‐human atrial natriuretic peptide and α‐conotoxin ImI, were also successfully synthesized. During these syntheses, no side reactions of methionine (Met) and tryptophan (Trp) residues or the S‐acetamidomethyl (Acm) protecting group were detected. These results suggested that Npys‐OMe or its solid‐phase analog provides a new strategy for regioselective disulfide bond formation to assist the synthesis of complex disulfide‐rich peptides. Abstract : Solid‐phase disulfide formation : A new disulfide‐forming agent based on the finding that alkoxy 3‐nitro‐2‐pyridinesulfenates (Npys‐OR) can mildly oxidize thiol groups has been developed. As a representative compound, Npys‐OMe and its solid‐phase derivative produced the cyclic peptide oxytocin from its linear form in a good yield (92 %) with minimal oligomer formation. Other disulfide peptides, α‐human atrial natriuretic peptide and α‐conotoxin ImI, were also successfully synthesized.